Ancora su religione e scienza: Note in margine a una recente pubblicazione - Aguti, Andrea (Annali di studi religiosi, 2015)
The article, after some introductory remarks on the relationship between religion and science, its relevance and its main characteristics in the current debate, develops a critical analysis of the book of G. Straffelini, Manifesto per scettici (ma non troppo) in cerca di Dio (2014). It discusses Straffelini’s thesis on the relationship between religion and science in general, his way of conceiving the relationship between mind and body, and the compatibility between a naturalistic worldview and theism, with special regard to the problem of natural evil.